Development and kinematic analysis of Scotch Yoke Mechanism / Abdul Azim Mohd Sabri - Mohd Sabri, Abdul Azim (2022)
The Scotch Yoke Mechanism is an example of slider-crank mechanism. The Scotch Yoke is a mechanism for converting the linear motion of a slider into rotational motion or vice versa. It is made of aluminium and consists of a rotary element, called crank, with a graduated disc. The Scotch yoke mechanism is most commonly used in control valve actuators in high- pressure oil and gas pipelines, as well as in various internal combustion engines, such as the Bourke engine, Sy Tech engine and many hot air engines and steam engines. The Scotch Yoke Mechanism is to be consider more efficient because of the rotational motion spent more time at high point of its rotation than Piston part. Also, The Scotch yoke mechanism had a very simple mechanism by having a simple contracture and need less quantity of material to build